UPAYA DINAS LINGKUNGAN HIDUP DALAM PENGENDALIAN PENCEMARAN UDARA DI KOTA TANGERANG - Nurwita, Mala; Maesaroh, Maesaroh; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Air pollution control is an effort to prevent, overcome and restore air quality. Air pollution control efforts are carried out by the central government, local governments and those in charge of businesses. The purpose of this research is to describe the efforts of the Tangerang City Environmental Service in Controlling Air Pollution and to identify the Inhibiting and Encouraging Factors of Tangerang City Environmental Service in Controlling Air Pollution. This research uses descriptive qualitative research methods. The data collection technique is done by interview, observation and documentation related to the research. The results showed that the efforts of Tangerang City Environmental Service in controlling air pollution have not been effective. The inhibiting factor for Tangerang City Environmental Service in controlling air pollution is environmental characteristics. The driving factors for Tangerang City Environmental Service in controlling air pollution are managerial policies and practices. Recommendations that can be made to increase the success of Tangerang City Environmental Service in controlling air pollution are increasing socialization to the public in controlling air pollution and increasing the budget allocation for Tangerang City Environmental Service regarding efforts to control air pollution.